Increasing Health Literacy and Preventive Behavior Against Noncommunicable Diseases Through Community-Based Health Education and Screening among Indonesian Immigrants in Malaysia - Mulyani, Sri; Utami, Wiwik; Putri, Evita Muslima Isnanda; Azizah, Nur; Setianto, Rony (PT. Riset Press International, 2025)
Limited access to healthcare and health information has made Indonesian migrant workers in Malaysia vulnerable to noncommunicable diseases (NCDs). This community service project aimed to improve community health literacy and preventive behavior through interactive health education, screening, and cadre empowerment in Bukit Sungai Putih, Lembah Jaya Utara, Selangor, Malaysia. The program applied a participatory approach combining community health education and direct screening for hypertension, diabetes, and metabolic risks. A total of 120 participants attended education sessions followed by individual counseling and basic health checks. Results indicated a significant improvement in health knowledge and awareness, as participants were able to identify risk factors and expressed willingness to perform regular self-monitoring. Post-activity interviews revealed an increased sense of responsibility toward adopting healthy lifestyles and sustaining community health cadres. This initiative highlights the importance of integrating education, local participation, and screening as an effective model to strengthen health literacy and disease prevention among immigrant populations.